The relationship between entrepreneurial orientation and firm performance: Influence of family governance. Issue 4 (December 2017) - Lee, Tingko; Chu, Wenyi
Abstract: A growing number of recent studies highlight an avenue of entrepreneurship in family business. Previous studies have examined the relationship between entrepreneurial orientation (EO) and firm performance, and generate inconsistent results probably due to the omission of the moderating role of family governance. To explicitly address this gap, this study investigates how entrepreneurial orientation (EO) influences firm performance in the contingencies of family and nonfamily firms by considering the influence of family governance. Built on agency theory and stewardship theory, the empirical findings of this study show that EO is positively associated with the concurrent and sustaining performance of firms, and such positive relationships are particularly strong when family ownership is combined with active family management and control; while in passive family governance, the EO-performance relationship becomes insignificant. These findings suggest that the potential advantages of EO can be better realized in family firms because active family governance alleviates agency problems and facilitates stewardship within firms when family CEOs, family top management, family chairpersons, and family directors are in presence.